Spectroscopic analysis for polarization sensitive optical coherent tomography - Strąkowski, Marcin R.; Pluciński, Jerzy; Kosmowski, Bogdan B. (Photonics Letters of Poland, 2011)
Polarization Sensitive Optical Coherent Tomography (PS-OCT) is a novel optical method to examine a broad range of scattering materials. PS-OCT is an extension of OCT systems, which enables cross-sectional visualization of the device inner structure, as well as analysis of the polarization state of light backscattered from particular points inside the tested device. Polarization sensitive analysis is a very useful tool in OCT measurements. However, it brings a number of problems referring to measurement signal processing, birefringence changes of the investigated sample over the spectral width of a broadband light source. In this paper these problems have been discussed and possible solutions have been given. Full Text: PDF References A.F. Fercher, W. Drexler, C.K. Hitzenberg,"Optical coherence tomography - principles and applications", Rep. Prog. Phys. 66, 239 (2003)[CrossRef] M.R. Strąkowski, J. Pluciński, M. Jędrzejewska-Szczerska, R. Hypszer, M. Maciejewski, B.B. Kosmowski, Sens. and Actuat. A 142, 104 (2008) A. Szkulmowska, M. Szkulmowski, A. Kowalczyk, M. Wojtkowski,"Phase-resolved Doppler optical coherence tomography—limitations and improvements", Opt. Lett 33, 1425 (2008)[CrossRef] M. Wojtkowski, T. Bajraszewski, P. Targowski, A. Kowalczyk,"Real-time in vivo imaging by high-speed spectral optical coherence tomography", Opt. Lett. 28, 1745 (2003)[CrossRef] D. Stifter, P. Burgholzer, O. Höglinger, E. Götzinger, C. K. Hitzenberger, "Polarisation-sensitive optical coherence tomography for material characterisation and strain-field mapping", Appl. Phys. A 76, 947 (2003)[CrossRef] D. Stifter,"Beyond biomedicine: a review of alternative applications and developments for optical coherence tomography", Appl. Phys. B 88, 337 (2007)[CrossRef] D. Stifter, K. Wiesauer, M. Wurm, E. Schlotthauer, J. Kastner, M. Pircher, E. Götzinger, C.K. Hitzenberger,"Investigation of polymer and polymer/fibre composite materials with optical coherence tomography", Meas. Sci. Technol. 19, 074011 (2008)[CrossRef] K. Wiesauer, M. Pirchen, E. Gotzinger, C.K. Hitzenberger,"Investigation of glass–fibre reinforced polymers by polarisation-sensitive, ultra-high resolution optical coherence tomography: Internal structures, defects and stress", Comp. Science Techn. 67, 3051 (2007)[CrossRef] P. Targowski, B. Rouba, M. Góra, L. Tymańska-Widmer, J. Marczak, A. Kowalczyk,"Optical coherence tomography in art diagnostics and restoration", Appl. Phys. A 92, 1 (2008)[CrossRef] J. Pluciński, R. Hypszer, P. Wierzba, M. Strąkowski, M. Jędrzejewska-Szczerska, M. Maciejewski, B.B. Kosmowski, "Optical low-coherence interferometry for selected technical applications", Bulletin of the Polish Academy of Sciences Technical Sciences 56, 155 (2008) M. Strąkowski, Analiza stanu polaryzacji światła w układach optycznej tomografii koherentnej dla badań struktury materiałów optoelektronicznych i mikroelektronicznych (PhD Dissertation, WETI PG 2010) Ch. Kasseck, V. Jaedicke, N.C. Gerhardt, H. Welp, M.R. Hofmann,"Substance identification by depth resolved spectroscopic pattern reconstruction in frequency domain optical coherence tomography", Opt. Com. 283, 4816 (2010)[CrossRef] Ch. Kasseck, V. Jaedicke, N.C. Gerhardt, H. Welp, M.R. Hofmann,"Frequency domain optical coherence tomography with subsequent depth resolved spectroscopic image analysis", Proc. of SPIE 7554, 75542T (2010)[CrossRef] G. Latour, J. Moreau, M. Elias, J-M. Frigerio,"Micro-spectrometry in the visible range with full-field optical coherence tomography for single absorbing layers", Opt. Com. 283, 4810 (2010)[CrossRef]